FEMINISME DIGITAL: KEDUDUKAN PEREMPUAN PERSPEKTIF ISLAM - Dafis Heriansyah; Alif Salama Samsul; Muhammad Hasbi Hasadiqi; Akma Amelia Tiara; Asfa Fikriyah (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2024)
Feminism in the digital era has developed to encompass various issues and perspectives. However, the intersection between feminism and Islam is still a controversial topic of debate. This paper aims to explore the concept of digital feminism in the context of Islamic values ​​and principles. The Islamic framework understands the position of women in actualizing the concept of equality, suitability and harmony in the digital space. This research uses a qualitative research method with primary sources of the Qur'an and the hadith of the Prophet saw, while secondary sources are based on books, journals, and websites that are relevant to this research. The findings in this study indicate that; first, the challenges faced by women in the digital space, such as online harassment, gender-based discrimination, and marginalization of women. Second, the spirit of feminism spreads in the digital space so that this movement is increasingly growing and entering the lives of Muslim women. Third, the Islamic perspective on women is different from the concept offered by feminism, because Islam glorifies women based on their portion and nature. This research is expected to provide benefits regarding the role of women in the Islamic perspective. The limitations of this study are inseparable from the sources of information presented. Therefore, this study recommends that further researchers study the concept of women in Islam, that the role of women in Islam is different from the concept offered by feminism. Keywords: Digital; Feminism; Gender; Islam; Women